2005
DOI: 10.1073/pnas.0408482102
|View full text |Cite|
|
Sign up to set email alerts
|

Force mapping in epithelial cell migration

Abstract: We measure dynamic traction forces exerted by epithelial cells on a substrate. The force sensor is a high-density array of elastomeric microfabricated pillars that support the cells. Traction forces induced by cell migration are deduced from the measurement of the bending of these pillars and are correlated with actin localization by fluorescence microscopy. We use a multiple-particle tracking method to estimate the mechanical activity of cells in real time with a high-spatial resolution (down to 2 μm) imposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
656
3
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 699 publications
(700 citation statements)
references
References 34 publications
34
656
3
7
Order By: Relevance
“…The first experimental evidence of mechanosensing dates back more than 30 years when Harris et al [91] reported and measured cell contractile forces on flexible rubber membranes. Numerous other studies have followed this first report especially focused on developing systems to analyse the dynamics of cell-generated forces [92][93][94]. These forces fall within the 1 pN -1 nN Table 2.…”
Section: Mechano-cue-mediated Crosstalkmentioning
confidence: 99%
“…The first experimental evidence of mechanosensing dates back more than 30 years when Harris et al [91] reported and measured cell contractile forces on flexible rubber membranes. Numerous other studies have followed this first report especially focused on developing systems to analyse the dynamics of cell-generated forces [92][93][94]. These forces fall within the 1 pN -1 nN Table 2.…”
Section: Mechano-cue-mediated Crosstalkmentioning
confidence: 99%
“…Recent advances in the development of two-dimensional model systems for studying cell-substrate mechanics of single cells have been reported by several groups [23,24,[37][38][39]. Among various biomaterials, polyacrylamide-based hydrogel (PAG), which can be engineered with variable chemical and mechanical properties, has proved to be an ideal experimental system for such study [40].…”
Section: Introductionmentioning
confidence: 99%
“…cell sheet, which is actually involved in major biological processes such as morphogenesis, wound healing and tissue repair is not thoroughly understood [19][20][21]. A recent study has shown that the distribution and magnitude of the CTF concentrates on the periphery of the cell colony on planar substrates [22,23]. Another study of an advancing epithelial cell sheet has demonstrated that the CTF in at its leading edge during migration is predominately driven by cells at the rear end instead of those at the leading edge [24].…”
Section: Introductionmentioning
confidence: 99%
“…Nous avons corrélé deux types essentiels d'informations ( Figure 1) : les forces dévelop-pées par les cellules sur le substrat et l'activité des RhoGTPases dans le plan basal des cellules. Les cellules sont déposées sur un tapis de micropiliers dont la déflexion renseigne sur les forces mises en jeu (amplitude et direction), ce qui permet d'obtenir une carte dynamique des forces [9]. Des biosenseurs moléculaires [10], dont la détection est basée sur une technique FRET (fluorescence resonance energy transfer), sont utilisés afin de déterminer l'activité des RhoGTPases RhoA et Rac1.…”
unclassified
“…Ces sondes renseignent sur la conformation des GTPases via l'interaction intramoléculaire de deux fluorophores. Les forces sont mesurées par la déflexion des piliers souples sur lesquels les cellules migrent [9]. La position du sommet de ces piliers (proportionnelle à la force qui y est appliquée) est mesurée en fluorescence sur le canal rouge (Cy5).…”
unclassified